Meta-Analysis of Factors Affecting Awareness of Citizenship Rights among Iranians - Akbar Zolfaghari; Taha Ashayeri (فصلنامه رفاه اجتماعی, 2022)
Introduction: Citizenship rights refers to a set of rules governing society in relation to politics, institutions, governments, and civil society. The main purpose of this study is to investigate the factors affecting the awareness of citizenship rights using meta-analysis. Method: The mechanism of conducting the research is meta-analysis-quantitative. The purpose of this method is to integrate, systematically review and standardize studies conducted in a specific field of research. The statistical population (materials) of this research comprises 32 research studies conducted in the years 1383-1400, of which 28 samples of research documents were found to be in accordance with the criteria of quantitative meta-analysis (correlation coefficient, sample size, significance level, research quality, validity of research, and survey). Findings: The results show that between political factors (political participation, political orientation, political awareness, and political trust), cultural (social awareness of rights, citizenship rights education, media consumption, and cultural capital), social (social trust, social participation, and social cohesion) and contextual variables (level of education, age, and socio-economic status) were found to have a significant relationship with the level of awareness of citizenship rights. Discussions: Increasing the level of people’s participation in the political and social spheres provides the basis for expanding the political awareness of citizens. Strengthening citizens’ political trust in the political system would lead to the development of citizenship rights. Education of citizenship rights provides the basis for increasing political-social awareness.